1992
DOI: 10.1007/bf00686301
|View full text |Cite
|
Sign up to set email alerts
|

Idarubicin metabolism and pharmacokinetics after intravenous and oral administration in cancer patients: a crossover study

Abstract: The pharmacokinetics and metabolism of 4-demethoxydaunorubicin (idarubicin, IDA) were studied in 21 patients with advanced cancer after i.v. (12 mg/m2) and oral (30-35 mg/m2) treatment according to a balanced crossover design. Patients were divided into four groups: subjects who showed normal liver and kidney function (group N), those who presented with normal kidney function and liver metastases (group L), those with kidney dysfunction (creatinine clearance, less than or equal to 60 l/h; group R), and those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…For instance, bupropion exposure is dramatically increased by 126% in patients with impaired kidney function, suggesting reduced metabolic clearance (Turpeinen et al, 2007). Moreover, a 30% decrease in the metabolic clearance of idarubicin was reported in patients with creatinine clearance of ,60 ml/min (Camaggi et al, 1992). This suggests that phase I reduction of drugs may be affected by kidney disease.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, bupropion exposure is dramatically increased by 126% in patients with impaired kidney function, suggesting reduced metabolic clearance (Turpeinen et al, 2007). Moreover, a 30% decrease in the metabolic clearance of idarubicin was reported in patients with creatinine clearance of ,60 ml/min (Camaggi et al, 1992). This suggests that phase I reduction of drugs may be affected by kidney disease.…”
Section: Discussionmentioning
confidence: 93%
“…Collectively, reductase enzymes play key roles in the biotransformation of diverse endogenous compounds such as bile acids, glucocorticoids, and prostaglandins, and numerous drugs Matsunaga et al, 2006;Oppermann, 2007;Malatkova and Wsol, 2014). Although the pharmacokinetics of several drugs that are reductase substrates, including idarubicin (Camaggi et al, 1992) and bupropion (Turpeinen et al, 2007), are altered in patients with CKD, the effect of impaired kidney function on specific hepatic reductase enzymes has not been assessed to date.…”
Section: Introductionmentioning
confidence: 99%
“…Using a slightly different definition of mild-to-moderate liver dysfunction (AST 1.5-4ϫ ULN, ALT 1.5-8ϫ ULN, and ALP 1.5-2ϫ ULN), Camaggi et al [12] found no significant PK alterations. While the authors concluded that no dose reductions were required in the presence of mild-to-moderate hepatic impairment, the data were insufficient to make recommendations for patients with severe hepatic impairment.…”
Section: Idarubicinmentioning
confidence: 99%
“…IDA is metabolised in the liver and other tissues to its major metabolite, IDOL, which has been shown to be as active as IDA [2]. IDA also has the advantage of being available for oral administration [3,4]. In addition, IDA and IDOL are less affected by topoisomerase II-related multidrug resistance than daunorubicin [5].…”
Section: Introductionmentioning
confidence: 99%